Bringing theory into practice: seeking constitutive utopian potential in Astana - Thompson, James (ARCC Conference Repository, 2014)
Contemporary architectural and urban theorists have called for resurrecting a utopian spirit as a means of imbuing urban design with social imagination, which they argue is currently lacking and badly needed (cf. Harvey 2000, Pinder 2002, Coleman 2005, 2011, 2013, Hatuka and D'Hooghe 2007, Picon 2013). Toward this end, this essay poses the city of Astana, capital of Kazakhstan and host of Expo 2017, as a site to begin examining how utopian analytical frameworks might inform certain readings of the city, which could in turn guide practical design decisions. Western journalists to Kazakhstan's new capital city frequently label it ‘utopian', in the popular, disparaging sense. And allusions are often made to capital-relocation and nation-building projects from the modern era, with Astana representing a postmodernist or late capitalist variation on a theme ostensibly bound for social disaster. But if utopianism is deserving of reconsideration, as recent scholarship maintains, so is Astana. Recent academic literature and experiential accounts of Astana's urban growth, when considered alongside contemporary utopian theory, challenge hasty classifications. Indeed, Kurokawa's ‘flexible' development plan for Astana initially sought to avoid the totalizing tendency of modernist master plans. Moreover, despite the garish character, as seen through foreign eyes, the genuine hopefulness Astana evokes in its residents should not be cynically disregarded. For designers contributing to the Astana project, utopian praxis means taking seriously the city's ‘constitutive' utopian potential and developing designs that aim to foster inchoate opportunities for social development.